2009
DOI: 10.4054/demres.2009.20.16
|View full text |Cite
|
Sign up to set email alerts
|

The decline of son preference and rise of gender indifference in Taiwan since 1990

Abstract: This study explores the change of married women’s sex preference for children in Taiwan since 1990, finding that there was a substantial decline of son preference and rise of “gender indifference”, defined as feeling indifferent about children’s sex (as opposed to desiring an equal number of boys and girls, in which the sex of children is still a primary consideration). Results show that at the individual level female education was the strongest predictor for the preference; education was negatively associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 28 publications
5
55
1
1
Order By: Relevance
“…In South Korea, during a period of rapid economic growth in the 1980s, sex ratios became the highest in Asia, though this was attributed to the novelty of easy access to sex-selective abortion (Park and Cho 1995). Taiwan demonstrated a similar pattern in the 1990s (Lin 2009). China's sex ratio has increased since the 1980s virtually in parallel with its economic growth and now has the world's highest sex ratio with an estimated 32 million excess men under the age of 20 (Zhu et al 2009).…”
Section: Introductionmentioning
confidence: 64%
“…In South Korea, during a period of rapid economic growth in the 1980s, sex ratios became the highest in Asia, though this was attributed to the novelty of easy access to sex-selective abortion (Park and Cho 1995). Taiwan demonstrated a similar pattern in the 1990s (Lin 2009). China's sex ratio has increased since the 1980s virtually in parallel with its economic growth and now has the world's highest sex ratio with an estimated 32 million excess men under the age of 20 (Zhu et al 2009).…”
Section: Introductionmentioning
confidence: 64%
“…In China, this large surplus of young men is now reaching reproductive age, with consequences yet to be ascertained, because failure to marry and have children inevitably affects a man's social status and acceptance in society. These young men have low self-esteem, feel marginalized, lonely, withdrawn and depressed [32], leading the government to make efforts to reduce sex selection with some degree of success, since -according to recent surveys -there is a significant decline in son preference in East Asia [33,34].…”
Section: The Ethics Of Sex-selective Infanticides; a Pragmatic Countementioning
confidence: 99%
“…The co-residing proportion was 59.4% for Vietnamese wives and 55.8% for Indonesian wives, compared with 39.7%, 41.6%, and 45.7% for their Chinese, Thai, and Filipina counterparts, respectively. For reference Lin (2009) found from Taiwan's 2002 "National Survey on Knowledge, Attitude and Practice of Health Promotion" that 38% of currently married women in the 20-44 age group in Taiwan co-resided with their husbands' parents or their own parents.…”
Section: Formulation Of the Multivariate Model And Specification Of Ementioning
confidence: 99%
“…The proportion of the foreign wives with at least a college degree was as high as 39.3% for the Filipinas, compared with only 3.6% for the Vietnamese and 5.1% for the Indonesians. For reference Lin (2009) showed that 29% of Taiwan's currently married women in the 20-44 age group in 2002 had more than 12 years of education.…”
Section: Formulation Of the Multivariate Model And Specification Of Ementioning
confidence: 99%
See 1 more Smart Citation